Efficacy and safety of high-dose lanreotide autogel in patients with progressive pancreatic or midgut neuroendocrine tumours: CLARINET FORTE phase 2 study results. (November 2021) - Pavel, Marianne; Ćwikła, Jaroslaw B.; Lombard-Bohas, Catherine; Borbath, Ivan; Shah, Tahir; Pape, Ulrich F.; Capdevila, Jaume; Panzuto, Francesco; Truong Thanh, Xuan-Mai; Houchard, Aude; Ruszniewski, Philippe
Abstract: Introduction: This prospective, single-arm, phase 2 study assessed the efficacy and safety of lanreotide autogel (LAN) administered at a reduced dosing interval in patients with progressive neuroendocrine tumours (NETs) after LAN standard regimen. Methods: Patients had metastatic or locally advanced, grade 1 or 2 midgut NETs or pancreatic NETs (panNETs) and centrally assessed disease progression on LAN 120 mg every 28 days. They were treated with LAN 120 mg every 14 days for up to 96 weeks (midgut cohort) or 48 weeks (panNET cohort). The primary end-point was centrally assessed progression-free survival (PFS). PFS by Ki-67 categories was analysed post hoc. Secondary end-points included quality of life (QoL) and safety. Results: Ninety-nine patients were enrolled (midgut, N = 51; panNET, N = 48). Median (95% CI) PFS was 8.3 (5.6–11.1) and 5.6 (5.5–8.3) months, respectively. In patients with Ki-67 ≤ 10%, median (95% CI) PFS was 8.6 (5.6–13.8) and 8.0 (5.6–8.3) months in the midgut and panNET cohorts, respectively. Patients' QoL did not deteriorate during the study. There were no treatment-related serious adverse events and only two withdrawals for treatment-related adverse events (both in the panNET cohort). Conclusions: In patients with progressive NETs following standard-regimen LAN, reducing the dosing interval to every 14 days provided encouraging PFS, particularly in patients with a Ki-67 ≤ 10% (post hoc); no safety concerns and no deterioration in QoL were observed. Increasing LAN dosing frequency could therefore be considered before escalation to less well-tolerated therapies. Graphical abstract: Image 1 Highlights: Prospective trial of lanreotide autogel 120 mg every 14 days in progressive neuroendocrine tumours (NETs). Median (95% confidence interval) progression-free survival (months): pancreatic NETs 5.6 (5.5–8.3); midgut NETs 8.3 (5.6–11.1). Patients with disease control on increased lanreotide dose had durable benefits. No new safety concerns with lanreotide at reduced dosing interval were observed. No deterioration in the quality of life.